Percutaneous coronary intervention versus coronary artery bypass grafting in patients with three-vessel or left main coronary artery disease: 10-year follow-up of the multicentre randomised controlled SYNTAX trial. Issue 10206 (12th October 2019) - Thuijs, Daniel J F M; Kappetein, A Pieter; Serruys, Patrick W; Mohr, Friedrich-Wilhelm; Morice, Marie-Claude; Mack, Michael J; Holmes, David R; Curzen, Nick; Davierwala, Piroze; Noack, Thilo; Milojevic, Milan; Dawkins, Keith D; et al.
Summary: Background: The Synergy between PCI with Taxus and Cardiac Surgery (SYNTAX) trial was a non-inferiority trial that compared percutaneous coronary intervention (PCI) using first-generation paclitaxel-eluting stents with coronary artery bypass grafting (CABG) in patients with de-novo three-vessel and left main coronary artery disease, and reported results up to 5 years. We now report 10-year all-cause death results. Methods: The SYNTAX Extended Survival (SYNTAXES) study is an investigator-driven extension of follow-up of a multicentre, randomised controlled trial done in 85 hospitals across 18 North American and European countries. Patients with de-novo three-vessel and left main coronary artery disease were randomly assigned (1:1) to the PCI group or CABG group. Patients with a history of PCI or CABG, acute myocardial infarction, or an indication for concomitant cardiac surgery were excluded. The primary endpoint of the SYNTAXES study was 10-year all-cause death, which was assessed according to the intention-to-treat principle. Prespecified subgroup analyses were performed according to the presence or absence of left main coronary artery disease and diabetes, and according to coronary complexity defined by core laboratory SYNTAX score tertiles. This study is registered with ClinicalTrials.gov, NCT03417050 . Findings: From March, 2005, to April, 2007, 1800 patients were randomly assigned to the PCI (n=903) or CABG (n=897) group. Vital status information at 10 years was complete for 841 (93%) patients in the PCI group and 848 (95%) patients in the CABG group. At 10 years, 248 (28%) patients had died after PCI and 212 (24%) after CABG (hazard ratio 1·19 [95% CI 0·99–1·43], p=0·066). Among patients with three-vessel disease, 153 (28%) of 546 had died after PCI versus 114 (21%) of 549 after CABG (hazard ratio 1·42 [95% CI 1·11–1·81]), and among patients with left main coronary artery disease, 95 (27%) of 357 had died after PCI versus 98 (28%) of 348 after CABG (0·92 [0·69–1·22], pinteraction =0·023). There was no treatment-by-subgroup interaction with diabetes (pinteraction =0·60) and no linear trend across SYNTAX score tertiles (ptrend =0·20). Interpretation: At 10 years, no significant difference existed in all-cause death between PCI using first-generation paclitaxel-eluting stents and CABG. However, CABG provided a significant survival benefit in patients with three-vessel disease, but not in patients with left main coronary artery disease. Funding: German Foundation of Heart Research (SYNTAXES study, 5–10-year follow-up) and Boston Scientific Corporation (SYNTAX study, 0–5-year follow-up).